Pengaruh Penggunaan Media Iklan pada Instagram Terhadap Keterampilan Menulis Teks Persuasif Siswa Sekolah Menengah Pertama - A. Nurwahida Asmi Safitri; Hajrah Hajrah; Usman Usman (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract. This study aims to prove the effect of using advertising media on Instagram on the skills of writing persuasive texts for Class VIII students of SMP Negeri 4 Mare, Bone Regency. This research is a quantitative type with a pre-experimental design. The population of this study were students of class VIII SMP Negeri 4 Mare, Bone Regency. The data in this study are the pretest and posttest values. The data analysis technique used is descriptive statistical analysis and non-parametric analysis. The results of the study through the Wilcoxon Test using SPSS version 21 revealed that there was a significant positive effect on the use of advertising media on Instagram on the persuasive text writing skills of Class VIII students of SMP Negeri 4 Mare Bone Regency as evidenced by the results of the Wilcoxon Test Output showing the Asymp value. Sig. (2-tailed) of 0.000 <probability value (α) 0.05.Keywords: Persuasive Text Writing Skills, Advertising Media on Instagram